2017
DOI: 10.1016/j.neuint.2016.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Targeting antioxidant enzyme expression as a therapeutic strategy for ischemic stroke

Abstract: During ischemic stroke, neurons and glia are subjected to damage during the acute and neuroinflammatory phases of injury. Production of reactive oxygen species (ROS) from calcium dysregulation in neural cells and the invasion of activated immune cells are responsible for stroke-induced neurodegeneration. Scientists have failed thus far to identify antioxidant-based drugs that can enhance neural cell survival and improve recovery after stroke. However, several groups have demonstrated success in protecting agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 113 publications
0
54
0
1
Order By: Relevance
“…During this study, we used pretreatment of gerbils with laminarin and found that SOD1 and SOD2, as endogenous antioxidant enzymes, were markedly increased in CA1 pyramidal neurons before and after IR induction. It has been suggested that increased endogenous antioxidant enzymes prevent the accumulation of ROS [41] and can protect against ischemic injuries [42]. To investigate whether increased SODs protect neurons from IR injury, we examined levels in DHE (a probe to detect superoxide anions) and HNE (a product of lipid peroxidation), as indicators of oxidative stress in the laminarin-IR group and found they were significantly more alleviated in the CA1 pyramidal neurons than those in the vehicle-IR group.…”
Section: Discussionmentioning
confidence: 98%
“…During this study, we used pretreatment of gerbils with laminarin and found that SOD1 and SOD2, as endogenous antioxidant enzymes, were markedly increased in CA1 pyramidal neurons before and after IR induction. It has been suggested that increased endogenous antioxidant enzymes prevent the accumulation of ROS [41] and can protect against ischemic injuries [42]. To investigate whether increased SODs protect neurons from IR injury, we examined levels in DHE (a probe to detect superoxide anions) and HNE (a product of lipid peroxidation), as indicators of oxidative stress in the laminarin-IR group and found they were significantly more alleviated in the CA1 pyramidal neurons than those in the vehicle-IR group.…”
Section: Discussionmentioning
confidence: 98%
“…Cerebral ischaemia ignites a complex, destructive cascade (Figure ) (Amantea, Greco, Micieli, & Bagetta, ; Davis & Pennypacker, ). Interruption of substrate and O 2 delivery stifles ATP production, causing Gibbs free energy of ATP hydrolysis (Δ G ATP ), the thermodynamic driving force for electrolyte transport and other critical cellular processes, to collapse.…”
Section: Adaptation To Intermittent Hypoxia: Robust Cerebroprotectionmentioning
confidence: 99%
“…Cerebral ischaemia ignites a complex, destructive cascade ( Figure 1) (Amantea, Greco, Micieli, & Bagetta, 2018;Davis & Pennypacker, 2017 Damaged neurons release purine nucleotides that provoke microglia to release inflammatory cytokines, drawing macrophages to the lesion (Iadecola & Anrather, 2011). These mechanisms culminate in death of brain parenchyma.…”
Section: Injury Mechanisms and Treatment Challenges Of Strokementioning
confidence: 99%
“…While the immunoreactivities of both MT-1/2 and MT-3 stained dominantly in glial cells and were decreased in the spinal cords with ALS patients, 113) another report showed a high expression of MT-3 in ALS. 114) It has been reported that treatment with cytokine leukemia inhibitory factor increases MT-3 expression in glia and boosts expression of superoxide dismutase 3 in neurons. 115) Through such cell-specific upregulation, various factors might have the potential to protect multiple cell types against ROS injury.…”
Section: Motor Neuron Diseases: Spinal Muscular Atrophy and Amyotrophmentioning
confidence: 99%
“…114) It has been reported that treatment with cytokine leukemia inhibitory factor increases MT-3 expression in glia and boosts expression of superoxide dismutase 3 in neurons. 115) Through such cell-specific upregulation, various factors might have the potential to protect multiple cell types against ROS injury. These reports indicate that MTs may have therapeutic potential against motor neuron diseases; however, there is much room for further research.…”
Section: Motor Neuron Diseases: Spinal Muscular Atrophy and Amyotrophmentioning
confidence: 99%